Consolidatory ablative stereotactic body radiation therapy after induction chemotherapy for unresectable pancreatic cancer: A single center experience - Lee, Hye In; Kang, Hyun-Cheol; Chie, Eui Kyu (Frontiers in Oncology, 2022)
Background and purpose: Consolidatory radiotherapy in form of stereotactic body radiation therapy (SBRT) with an ablative dose following induction chemotherapy is emerging as a promising treatment scheme for unresectable pancreatic cancer. Outcomes of given treatment at a single center for contiguous patients with unresectable pancreatic cancer were evaluated to build the optimal treatment strategy. Materials and Methods: In this retrospective study, a total of 50 patients with unresectable pancreatic cancer who underwent induction chemotherapy and ablative dose SBRT were included. SBRT dose was 40–50 Gy in five fractions. Two strategies were adopted to adhere to the organs at risk (OAR) dose constraints: simultaneous integrated protection (SIP) technique and magnetic resonance (MR)-guided adaptive technique. Overall survival (OS) and local progression-free survival (LPFS) were calculated from the start date of SBRT. Results: The median follow-up period for survivors was 21.1 months (range, 6.2–61.0 months). Eleven (22.0%) patients underwent resection after SBRT, which were all R0 resection. In patients with non-metastatic disease, the median OS was 26.5 months (range, 4.1–61.0 months), and the 1- and 3-year LPFS were 90.0% (95% confidence interval [CI], 72.0–96.7%) and 57.4% (95% CI, 31.7–76.4%), respectively. Patients with oligometastatic disease had inferior survival outcomes, but there was no survival difference among responders to induction chemotherapy. In the multivariable analysis, tumor size ≤4 cm, non-metastatic status, and good response to induction chemotherapy were associated with improved LPFS. In dosimetric analysis, GTV Dmin ≥50.5 Gy was the strongest prognosticator against local progression. Grade ≥3 adverse events occurred in two (4.0%) patients with non-adaptive RT, but none in patients with MR-guided adaptive RT. Conclusion: Ablative dose SBRT following induction chemotherapy is an effective strategy for selected patients with unresectable pancreatic cancer. The SIP technique and MR-guided adaptive RT were attributed to minimizing the risk of adverse events. Further studies are needed to identify the best candidates for consolidatory SBRT in unresectable pancreatic cancer.